Maxillary implant overdentures on two or four implants: a prospective randomized cross-over clinical trial of implant and denture success and survival - Kappel, Stefanie; Klotz, Anna-Luisa; Eberhard, Lydia; Lorenzo Bermejo, Justo; Rammelsberg, Peter; Giannakopoulos, Nikolaos Nikitas (Clinical oral implants research, 2021)
Objectives To determine implant survival and success of four conventionally but initially asynchronously loaded implants in implant-supported overdentures for the edentulous maxilla, in participants with opposing mandibular two-implant overdentures. Material and methods Twenty-six participants received four implants in the region of the maxillary canines and molars. After healing, 24 of these participants (mean age: 68.3 years) were randomly allocated to one of two treatment groups, and the adapted overdenture was attached to two unsplinted cylindrical attachments. The other two matrixes remained unattached to the implants for 3 months. After this period, the other two implants were loaded for 3 months (cross-over design). Then, all four implants were loaded for another 3 months. Kaplan-Meier curves were used to evaluate survival and success of implants and dentures. Results During the active prosthetic study phase, three participants lost one implant. Two participants lost three implants during the recall period. Implant survival after loading was 93.8% after a mean observation period of 3.1 years. Denture survival was 100%, but denture success was 95.8%, due to major prosthetic complications. Most participants preferred four implants to two. Conclusions Within the limitations of the study, it can be concluded that maxillary implant overdentures on two or four implants are both recommendable treatment options. Two posterior implants are not superior to two anterior implants under overdentures retained by unsplinted cylindrical attachments. Implant and prosthetic complications and aftercare measures are common but are mostly easy to handle. However, 23 of the 24 participants preferred the 4-implant maxillary overdenture.